1970
DOI: 10.1136/bmj.1.5693.400
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Studies and Clinical Observations During L-Dopa Treatment of Parkinson's Disease

Abstract: Summary: Twenty-two patients with. Parkinson's disease were treated for the periods, of up to six months with L-dopa. In nine of the male patients metabolic observations were made after oral administration of '4C-L-dopa.Peak serum levels of total radioactivity represented small fractions of the dose given and occurred at one to two hours after ingestion. Two-thirds of the dose was excreted as metabolites in urine in eight hours. Insignificant fractions of the dose were excreted in stool and expired air. These … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0
1

Year Published

1970
1970
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(14 citation statements)
references
References 6 publications
1
12
0
1
Order By: Relevance
“…Two patients aged less than 65, however, continued to show increasing benefit up to 12 months of continuous treatment. This finding confirms the observations of Yahr, Duvoisin, Hoehn, Schear, and Barrett (1968) and Peaston and Bianchine (1970). No patient who ultimately benefited from treatment with levodopa has failed to show improvement before the threemonth evaluation.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Two patients aged less than 65, however, continued to show increasing benefit up to 12 months of continuous treatment. This finding confirms the observations of Yahr, Duvoisin, Hoehn, Schear, and Barrett (1968) and Peaston and Bianchine (1970). No patient who ultimately benefited from treatment with levodopa has failed to show improvement before the threemonth evaluation.…”
Section: Discussionsupporting
confidence: 89%
“…Two patients with arteriosclerotic Parkinsonism failed to show any response to treatment with levodopa. Cotzias et al (1969) were unable to find any correlation between age or arteriosclerosis and response to levodopa but subsequent workers have shown that degree of improvement is inversely related to both age (Peaston and Bianchine, 1970) and hypertension (Hughes, Polgar, Weightman, and Walton, 1971). Our results suggest that elderly or arteriosclerotic patients suffering from a Parkinsonian syndrome respond less well to levodopa than patients who show uncomplicated features of idiopathic Parkinsonism.…”
Section: Discussionmentioning
confidence: 98%
“…It would nevertheless appear that under the experimental conditions described exposure to ultrasound does produce appreciable damage to human chromosomes. , 1970, 4, 93-94 The efficacy of L-3, 4,dihydroxyphenylalanine (L-dopa) in most patients with Parkinson's disease has been documented repeatedly (Calne et al, 1969;Cotzias et al, 1969;Mawdsley, 1970;Peaston and Bianchine, 1970a). Little is known, however, about the significant number of patients who do not respond (20-30%).…”
mentioning
confidence: 99%
“…Very low levels of orally administrated levodopa are excreted in faeces indicating a high absorption of levodopa (41,42). When taken orally C max of levodopa in blood is seen after 1-2 hours (41,43) and levodopa is mainly excreted via the kidneys with two-thirds elimination within 8 hours (41) and 85 % elimination within 24 h (43). Only app.…”
Section: Levodopa In the Peripherymentioning
confidence: 99%